Strategies to Improve Halal Tourism in Indonesia During The Pandemic Covid-19 - Anita Musfiroh; Mugiyati Mugiyati; Aldi Khusmufa Nur Iman (ITB AAS INDONESIA Surakarta, 2021)
The Covid 19 has had an impact on various sectors of human life. One of them is the tourism sector. The tourism industry which is predicted to be the second largest source of foreign exchange contributions for Indonesia has experienced a drastic decline. Likewise, the halal tourism sector has also been severely affected by the Covid 19 pandemic. This is because the key to developing the halal tourism sector is Muslim tourists or visitors who come. To revive the tourism sector, it requires a number of strategies prepared by the government to improve the economy in the halal tourism sector. The purpose of writing this article is to find out how the impact of Covid 19 on the halal tourism sector and how the strategy to revive the halal tourism sector during the Covid 19 pandemic. The method used in this study is a qualitative method with data collection techniques used is literature study. The results of the study state that the strategy to restore the halal tourism sector from the Covid 19 pandemic consists of 3 stages and recommendations for implementing health protocols. The existence of this strategy and also the health protocol is expected by the enthusiastic community to return to enliven the tourism sector, including halal tourism.